2020
DOI: 10.1002/14651858.cd013497.pub2
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF (granulocyte macrophage colony-stimulating factor) supplementation in culture media for women undergoing assisted reproduction

Abstract: GM-CSF (granulocyte macrophage colony-stimulating factor) supplementation in culture media for women undergoing assisted reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Unclear if beneficial or no effect (low quality)40 Endometrial scratch (n = 4)…”
mentioning
confidence: 99%
“…Unclear if beneficial or no effect (low quality)40 Endometrial scratch (n = 4)…”
mentioning
confidence: 99%
“…A recent Cochrane systematic review and meta-analysis showed that the addition of GM-CSF in the embryo culture medium did not increase LBR (OR 1.19; 95% CI 0.93 to 1.52; 2 RCTs; n = 1432; I 2 = 69%; low-quality evidence) and did not reduce miscarriage rate (OR 0.75; 95% CI 0.41 to 1.36; 2 RCTs; n = 1432; I 2 = 0%; low-quality evidence) compared to culture in conventional media without GM-CSF ( Armstrong etal. , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Cochrane review analysed the data on multiple gestations (OR 1.24; 95% CI 0.73 to 2.10; 2 RCTs; n = 1432; I 2 = 35%; very low-quality evidence), preterm birth (OR 1.20; 95% CI 0.70 to 2.04; 2 RCTs; n = 1432; I 2 = 76%; very low-quality evidence), birth defects (OR 1.33; 95% CI 0.59 to 3.01; I 2 = 0%; 2 RCTs; n = 1432; low-quality evidence), and aneuploidy (OR 0.34; 95% CI 0.03 to 3.26; I 2 = 0%; 2 RCTs; n = 1432; low-quality evidence) and reported no increased incidence of any adverse events but with a large degree of uncertainty ( Armstrong etal. , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the implantation rates and pregnancy rates were different among investigated studies. According to a Cochrane meta-analysis, there was no evidence that GM-CSF supplemented culture media had any superiority compared to standard media in terms of clinical outcomes ( 32 ). Furthermore, only one large, randomized, controlled trial ended with positive results in LBRs between the study and control groups ( 26 ).…”
Section: Discussionmentioning
confidence: 99%